Potensi Ekstrak Bunga Telang (Clitoria ternatea Linn) sebagai Pewarna pada Produk Tape Ketan: Potential of Telang Flower Extract (Clitoria ternatea Linn) as a Colorant on Sticky Rice Tapai Products - Sarlina Palimbong; Arlissha Sharon Pariama (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Telang flower or Clitoria ternatea L is a kind of legume that is vines and easily planted and has the potential as a source of antioxidants. The blue substance contained in telang flowers has high anthocyanin content. Anthocyanin can be useful for health and in the world of food. This study was conducted to determine the potential of telang flower extract as a colorant on tape. Telang flowers are extracted by maceration method using citric acid with variations concentration 0, 0,25, 0,50, 0,75 and 1%. After extracting, each extract of telang flowers was tested for antioxidants by the DPPH method (1.1 diphenyl-2-picrihydazyl) and was applied as a coloring agent on tape products. IC50 value of telang flower extract before being applied was 53.61 ppm which is included in the category of having strong antioxidants, whereas after being applied to coloring on tape the IC50 value was 142.8 ppm which was included in the category of moderate antioxidant content. Organoleptic test results on 50 untrained panelists showed that in the color aspect the panelists tended to prefer coloring from a concentration of 1%, while in the aspect of aroma, taste, and texture the panelists tended to be neutral.